Concept of Hayat, Iman, Ruh, Qadar and al-Kawn in the Teaching of Khawaja Yusuf Hamadani: An Analytical and Descriptive Study - Mansurov, Fatkhiddin; Khan, Musaddiq Majid (Probe and Find Forum, Lahore, 2016)

(untitled)
This study proposes exposition to the teachings and influence of Khawājah Yusuf Hamadānī who is a prominent SËfÊ sheikh of the 11-12th centuries on the subsequent formation of Sufi tarīqahs in Central Asia. This study is the thought of Khalwah dar Anjuman that means to be with people while keeping Allah in heart. By studying his interpretations to the sufi terms like Hayāt, Īmān, Rūh, Qadar and al-Kawn. We may clearly see that he would always attempt to practice his religion completely and never neglect any laws of Islam. His teachings did not approve of being drunk spiritually and he did not claim any miracles which are experienced by some other saints. This study may be a reference for further researches that might be conducted on History of Sufism, Islamic History and other related areas.